Impact of Coping Stress, Digital Leadership and Learning Culture on Employee Engagement of Millennial Generation in Ditpolair Polda Metro Jaya - Restu Restu; Andriyanto Eko Wibowo; Justine Tanuwijaya (Budapest International Research and Critics University, 2022)
The purpose of this study is to measure the employee engagement level of millennial generation employees at Ditpolair Polda Metro Jaya and compare with millennial generation outside Ditpolair Polda Metro Jaya, then prove the influence of stress coping, digital leadership and learning culture on employee engagement of millennial generation employees at Ditpolair Polda Metro Jaya. The research method used is survey with questionnaire distribution to 104 respondents, analyze data by kruskal-wallis test, and multiple regression. The results obtained are stress coping are not significantly different between Ditpolair Polda Metro Jaya and comparison institution, while employee engagement, digital leadership and learning culture are significantly different. The results showed that stress had no significant effect, while digital leadership and learning culture had a significant effect on employee engagement.